High complex crane system design - Wong, Ryan Xin Jian (2014)
Mobile cranes are extremely valuable heavy-duty vehicles in many engineering applications due to their versatility - that is having the ability to lift extremely heavy loads and yet, travel around like any other vehicle. However, one of the biggest disadvantages is its sheer size with respect to civilian road which makes it hard to maneuver around especially in crowded cities.